Metacognitive beliefs, mood symptoms, and fatigue four years after stroke: An explorative study. - Synne G Pedersen; Audny Anke; Oddgeir Friborg; Marte C Ørbo; Mari T Løkholm; Marit Kirkevold; Guri Heiberg; Marianne B Halvorsen (PLoS ONE, 2024)
Objective This cross-sectional study investigated the relationship between metacognition and mood symptoms four years post-stroke and examined fatigue as a potential moderator for this relationship. Methods A number of 143 participants completed a survey that included the Hospital Anxiety and Depression Scale (HADS), the Metacognition Questionnaire-30 (MCQ-30), the Fatigue Severity Scale (FSS), and the modified Rankin Scale (mRS) (functional status) four years after stroke. Multiple regression analyses adjusting for demographic and stroke-specific covariates were performed with anxiety and depression as dependent variables and fatigue as a moderator. Results The proportions of participants satisfying the caseness criteria for anxiety and depression were 20% and 19%, respectively, and 35% reported severe fatigue. Analysed separately, all MCQ-30 subscales contributed significantly to anxiety, whereas only three MCQ-30 subscales contributed significantly to depression. In the adjusted analyses, the MCQ-30 subscales 'positive beliefs' (p < 0.05) and 'uncontrollability and danger' (p < 0.001), as well as fatigue (p < 0.001) and functional status at four years (p < 0.05) were significantly associated with anxiety symptoms. Similarly, the MCQ-30 subscales 'cognitive confidence' (p < 0.05) and 'self-consciousness' (p < 0.05), as well as fatigue (p < 0.001), stroke severity at baseline (p < 0.01), and functional status at four years (p < 0.01) were significantly associated with depression symptoms. Fatigue did not significantly moderate the relationship between any MCQ-30 subscale and HADS scores. Conclusion Maladaptive metacognitions were associated with the mood symptoms of anxiety and depression, independent of fatigue, even after controlling for demographic and stroke-specific factors. Future studies should implement longitudinal designs to determine whether metacognitions precede anxiety or depression after a stroke, and more strongly indicate the potential of metacognitive therapy for improving the mental health of individuals after a stroke.